Use of the Thrombolysis in Myocardial Infarction Risk Index for Elderly Patients With ST-Segment Elevation Myocardial Infarction - Fu, Bingqi; Wei, Xuebiao; Wang, Qi; Yang, Zhiwen; Chen, Jiyan; Yu, Danqing (Frontiers in Cardiovascular Medicine, 2021)
Background: Thrombolysis in Myocardial Infarction (TIMI) Risk Index (TRI) is a simple risk assessment tool for patients with ST-segment elevation myocardial infarction (STEMI). However, its applicability to elderly patients with STEMI undergoing percutaneous coronary intervention (PCI) is uncertain. Methods: This was a retrospective analysis of elderly (≥60 years) patients who underwent PCI for STEMI from January 2010 to April 2016. TRI was calculated on admission using the following formula: heart rate×(age/10)2/systolic blood pressure. Dis-crimination and calibration of TRI for in-hospital events and one-year mortality were analyzed. Results: Totally 1054 patients were divided into three groups according to the tertiles of the TRI: <27 (n=348), 27–36 (n=360) and >36 (n=346). The incidence of acute kidney injury (AKI; 7.8% vs. 8.6% vs. 24.0%, p<0.001), AHF (3.5% vs. 6.6% vs. 16.2%, p<0.001), in-hospital death (0.6% vs. 3.3% vs. 11.6%, p<0.001) and MACEs (5.2% vs. 5.8% vs. 15.9%, p<0.001) was significantly higher in the third tertile. TRI showed good discrimination for in-hospital death (area under the curve [AUC] = 0.804, p<0.001; Hosmer-Lemeshow p=0.302), which was superior to its prediction for AKI (AUC=0.678, p<0.001; Hosmer-Lemeshow p=0.121), and in-hospital MACEs (AUC=0.669, p<0.001; Hosmer-Lemeshow p=0.077). Receiver-operation characteris-tics curve showed that TRI>42.0 had a sensitivity of 64.8% and specificity of 82.2% for predicting in-hospital death. Kaplan-Meier analysis showed that patients with TRI>42.0 had higher one-year mortality (Log-rank=79.2, p< 0.001). Conclusion: TRI is suitable for risk stratification in elderly patients with STEMI undergoing PCI, and is thus of continuing value for an aging population.